(untitled) (New York, 2002)
Since its inception in 1915, the Best American series has become the premier annual showcase for the country's finest short fiction and nonfiction. For each volume, a series editor reads pieces from hundreds of periodicals, then selects between fifty and a hundred outstanding works. That selection is pared down to the twenty or so very best pieces by a guest editor who is widely recognized as a leading writer in his or her field. This unique system has helped make the Best American series the most respected -- and most popular -- of its kind. In his introduction to this year's collection, James Ellroy explores the differences between the novel and the short story. Included here are experts at both forms. Featuring renowned novelists like Stuart Kaminsky, Michael Connelly, Joe Gores, and Robert B. Parker, as well as veterans of this series like Brendan DuBois, Michael Downs, Joyce Carol Oates, and Clark Howard, this edition will delight readers with its wide variety and peerless quality.
Keywords: Detective and mystery stories, american